Assessing The Performance Of Sub-District Heads As Regional Apparatus In Local Governance: Evidence From Majalengka Regency - Mona Indrianie; Ine Mariane; Fadiya Nabila Putri (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The decentralization policy in Indonesia, mandated by Law No. 23 of 2014, has placed the Head of District as a strategic actor in local governance, particularly in delivering public services, coordinating inter-unit functions, and maintaining social stability. Despite this mandate, performance gaps remain, as shown by community dissatisfaction in Majalengka District. This study aims to analyze the performance of the Head of District in Majalengka within the framework of regional autonomy. Grounded in performance, public service, and leadership theories, the research employs a qualitative approach with data collected through observation, interviews, documentation, and literature review. Data analysis follows Miles and Huberman’s model, supported by triangulation for validity. The findings reveal that while governance functions are generally effective and efficient, challenges persist in service optimization and delegation of authority. This study contributes to the literature by integrating multidimensional performance indicators and offers practical implications for enhancing district-level governance. Keywords: Head Of District, Performance, Local Governance